PENGARUH KUALITAS LAYANAN DAN PRODUK TERHADAP KEPUASAN DAN LOYALITAS MAHASISWA: (Studi Kasus di Universitas 17 Agustus 1945 Banyuwangi) - Tutut Hariyadi (Media Mahardhika, 2020)
Background research efforts should be made by the company or organization whether profit oriented or non-profit in anticipation of the competitive situation that is how to retain customers, retain customers because they cost less than attracting new customers. From this background, the researcher sought to prove that maintaining customer must be accompanied with efforts in managing the quality of services and products or programs of study to create customer satisfaction affecting loyalty. The data used in this study is the primary data from respondents through a questionnaire, with indicators for quality of service include:reliability, assurance, tangible, empathy and responsiveness. Indicators include the needs and benefits of products and quality. Indicators include the suitability of satisfaction on customer expectations with reality. Indicators include loyalty to say positive things and recommend to someone who needs information and encourage friends, relatives and close people. The population in this study were all students at the University August 17, 1945 which includes the armed Banyuwangi 2017, 2018 and 2019 some 905 people with a sample of 136 people. The variables used were the quality of service, product or course of study, satisfaction and loyalty. Analysis techniques using path analysis (path analysis). The results of the analysis stated that the quality of services and products or programs of study influence the satisfaction of students at the University August 17, 1945 Banyuwangi. And quality of services and products or programs of study influence the loyalty of students at the University August 17, 1945 Banyuwangi through intervening variable satisfaction.